Výuka sociální politiky a managementu ve studijních programech PDF UPOL - Skarupská, Helena (Univerzita Pardubice, 2008)
The contribution is focused to teaching of social policy and similar subjects and teaching management of human resources in curriculum of Faculty of Education Palacký University, Olomouc.
Keywords: social policy; management of human resources; curriculum